The Fermi pseudo-potential in one dimension - Coutinho, FAB; Nogami, Y.; Tomio, L.; Toyama, F. M. (Iop Publishing Ltd, 2004)
Wu and Yu recently examined point interactions in one dimension in the form of the Fermi pseudo-potential. on the other hand there are point interactions in the form of self-adjoint extensions (SAEs) of the kinetic energy operator. We examine the relationship between the point interactions in these two forms in the one-channel and two-channel cases. In the one-channel case the pseudo-potential leads to the standard three-parameter family of SAEs. In the two-channel case the pseudo-potential furnishes a ten-parameter family of SAEs.